EFFECT OF VALUE ADDED TAX (VAT), INCOME, PRICE AND PAYMENT METHODS AGAINST CONSUMER DEMAND ON SMARTPHONES - Tia Anggraini; Sri Yani Kusumastuti (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2022)
This study aims to estimate the influence of Value Added Tax (VAT), Income, Price and Payment Method on Demand. The data used is primary data using questionnaire techniques with data obtained through google forms. Sampling was carried out using purposive sampling techniques. In this study, a sample of 213 respondents was used. The analysis method used is SEM analysis using the AMOS 23 application. The results showed that Value Added Tax (VAT) has a negative influence on demand, Income has no influence on demand, Price has a negative influence on demand and Payment Methods have a positive effect on demand.